Ageing doctors. (25th January 2017) - Lillis, Steven; Milligan, Eleanor
Abstract : Doctors are neither more nor less susceptible than the general population to the effects of ageing. The relevance of deterioration with age depends on the nature of the work undertaken. Reduced muscle strength and visual and auditory deterioration can compromise clinical ability. Accumulation of chronic disease further reduces capacity. Cognitive decline is of particular importance, as good medical care requires considerable cognitive function. Patient safety is paramount, yet older doctors are an important part of the medical workforce and their value should be recognised. Changes in patient case mix, work place support systems and individual adjustments can assist safe practice. Deterioration in health should be acknowledged and requires proactive management. Current methods of ensuring competence are inadequate for supporting ageing doctors. A new initiative is recommended comprising collaboration between regulators, colleges and employing institutions to support the ageing doctor in providing safe and effective practice.